The crossroad - Lewis, Beverly, 1949- (Bethany House Publishers, 1999)
After the dramatic conclusion to his discovery of a long-lost postcard, journalist Philip Bradley simply cannot forget the Amish people he met while on assignment in Pennsylvania--particularly Rachel Yoder and her young daughter, Annie. Drawn back to Lancaster County over the Christmas holidays, Philip struggles with the vast gulf separating him from the beautiful Plain woman.